Penerapan Algoritma Zig Zag Pada Pemrosesan Kompresi File Citra Digital - Riduansyah Riduansyah; Kristian Siregar; Pristiwanto Pristiwanto (JURIKOM (Jurnal Riset Komputer), 2018)
Digital imagery requires development with several methods for storing images. Images often experience decreased resolutions during compression and de-compression. To reduce the storage size needed for high resolution digital photos, it is necessary to compress and thus reduce the file size. Compression is the process of eliminating data redundancy or transforming data into shapes that occupy little storage space. A standard JPEG is a collaboration between the International Telecommunication Union (ITU), the International Organization for Standardization (ISO), and the International Electrotechnical Commission (IEC). The Zig zag method for drawing a small number of devices is applied to an image with different brightness levels for values different from the bit rate (bpp) using the zig zag algorithm.